Effects of meaningful perceived inequality on wellbeing and the maintenance (or challenge) of the status quo - Rodríguez Bailón, Rosa (2025)
Today, nobody doubts that economic inequality is one of the defining features of current societies and has significant effects on them. While the economic impact of inequality has been analyzed, its psychological effects on individuals have been studied only recently. On the latter front, one line of research in social psychology focuses on the impact of subjective economic inequality on individuals’ health and well-being (e.g., status anxiety), while another focuses on political attitudes that might reinforce (e.g., populism) or attenuate (e.g., support for redistribution) inequality. This chapter leverages the state-of-the-art scientific research on subjective economic inequality to two ends. First, it sets the conceptual boundaries of meaningful perceived inequality (i.e., inequality that is meaningful for individuals) to understand the individual and social consequences of objective economic inequality. Second, it elaborates on the potential implications of meaningful inequality —especially that perceived at a specific level and closely experienced (e.g., perceived inequality in everyday life)— for the maintenance of (or challenge to) the unequal status quo. The chapter also presents evidence on the role of ideologies that legitimize (and challenge) unequal contexts.